2017
DOI: 10.1364/ol.42.000211
|View full text |Cite
|
Sign up to set email alerts
|

Strip-loaded horizontal slot waveguide

Abstract: We introduce a novel concept for an optical waveguide called a strip-loaded slot waveguide. It allows an extraordinary confinement of the field in a waveguide with an extremely tiny (vertical) cross section. Unlike conventional slot waveguides, the proposed configuration has potential for very low propagation losses. Its operation is demonstrated at telecommunication wavelengths and, in addition, it is fabricated by means of mass production compatible techniques: atomic layer deposition and nanoimprint replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…There is a very limited interaction of the optical field and the sidewall roughness of the strip. SLSW has been, moreover, integrated with some nano-and microstructures such as Y-junctions, ring resonators, and photonic-crystal-based structures [4][5]. In this paper, we design an AWG on SLSW structure at the center wavelength of 1550 nm for sensing application, and to the best of our knowledge, no SLSW-AWG has been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…There is a very limited interaction of the optical field and the sidewall roughness of the strip. SLSW has been, moreover, integrated with some nano-and microstructures such as Y-junctions, ring resonators, and photonic-crystal-based structures [4][5]. In this paper, we design an AWG on SLSW structure at the center wavelength of 1550 nm for sensing application, and to the best of our knowledge, no SLSW-AWG has been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer strips are ideal due to their relatively low refractive index and easiness to pattern. We have recently demonstrated that such a strip-loaded waveguide can be easily combined with a horizontal slot waveguide [2] in order to confine at the nanoscale the electric field in a low refractive index layer sandwiched between two high refractive index films [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The structure of film-loaded silicon nanowire optical rectangular waveguide (SNORW) is thoroughly discussed in the Section 2. Film-loaded waveguide having its advantage of high confinement factor and greater sensitivity is compared to conventional dielectric waveguide without any film [27][28][29]. This silicon nanowire-based film-loaded optical rectangular waveguide is termed as film-loaded SNORW.…”
Section: Introductionmentioning
confidence: 99%